What drives the correlation between stock and bonds - Hudson, Jeremy (Department of Finance and Tax, 2025)
This research paper investigates the correlation between stocks and bonds in South Africa between 2002 and 2020and further explores the macroeconomic variables which determine these stock bond correlations. South African stock returns are proxied by the FTSE/JSE All Share Total Return Index (JALSHTR Index) and the South African bond returns are proxied by FTSE/JSE ALBI Total Return Index (ALBITR Index). In addition, this paper includes the following indices in the analysis: JSE Industrial 25 Index Total Return Value (INDI25TR Index), FTSE/JSE South African Listed Property Total Return Index (JSAPYTR), JSE Financials 15 Index Total Return Value (FINI15TR Index).The correlations were calculated for each of the indices against the bond index over the sample period as well as rolling five year correlations. A regression analysis was conducted to investigate the regression to address the second research question The findings indicate a positive relationship between the bond index (ALBITR Index) and all the different types of equity indices (JALSHTR Index, INDI25TR Index, JSAPYTR, FINI15TR Index) over the sample period. The regression results reveal that long-term expected inflation was the only variable with a positive relationship to stock-bond correlations. All other variables (short term expected inflation, unexpected inflation, real interest rates, binary business cycles variable) exhibited a negative relationship with stock bond correlation. The results suggest that macroeconomic variables have limited influence, as none of them were statistically significant at the 10% significance level. The key contribution of this research is investigating the stock-bond relationship within the South African context over the past two decades.